2019
DOI: 10.1021/acs.est.8b05446
|View full text |Cite
|
Sign up to set email alerts
|

Cryptosporidium Incidence and Surface Water Influence of Groundwater Supplying Public Water Systems in Minnesota, USA

Abstract: Regulations for public water systems (PWS) in the U.S. consider Cryptosporidium a microbial contaminant of surface water supplies. Groundwater is assumed free of Cryptosporidium unless surface water is entering supply wells. We determined the incidence of Cryptosporidium in PWS wells varying in surface water influence. Community and noncommunity PWS wells (n = 145) were sampled (n = 964) and analyzed for Cryptosporidium by qPCR and immunofluorescence assay (IFA). Surface water influence was assessed by stable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 41 publications
2
32
0
Order By: Relevance
“…In a recent study conducted in Minnesota, it was found that 40% of the 145 wells examined were contaminated with Cryptosporidium spp. ; furthermore, out of 45 samples sequenced, 41 were positive for C. parvum , 2 were positive for C. hominis , and 2 were positive for C. andersoni [27]. Following the examination of the 178 outbreaks that occurred in England and Wales between 2009 and 2017, it was highlighted that the transmission of the protozoan occurred mainly via recreational water, animal contact, environmental contact, person-to-person spread, drinking water and food.…”
Section: Resultsmentioning
confidence: 99%
“…In a recent study conducted in Minnesota, it was found that 40% of the 145 wells examined were contaminated with Cryptosporidium spp. ; furthermore, out of 45 samples sequenced, 41 were positive for C. parvum , 2 were positive for C. hominis , and 2 were positive for C. andersoni [27]. Following the examination of the 178 outbreaks that occurred in England and Wales between 2009 and 2017, it was highlighted that the transmission of the protozoan occurred mainly via recreational water, animal contact, environmental contact, person-to-person spread, drinking water and food.…”
Section: Resultsmentioning
confidence: 99%
“…Cryptosporidium oocysts were investigated in several studies either alone or along with other intestinal parasites among different population groups [13][14][15][16], as well as, in the environment [17][18][19] and domestic animals [20,21]. In Jordan, studies on Cryptosporidium were conducted on normal and immunocompromised patients among different age groups [10,12,[22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…Cryptosporidium is a worldwide zoonotic apicomplexan protozoan parasite (1) infecting the gastrointestinal tract of a wide range of vertebrates, including humans, livestock, wild animals, and birds (2,3). The most common routes for Cryptosporidium transmission are direct fecal contamination or contaminated drink water that result in diarrhea in a variety of vertebrate hosts (4). In humans, this infection is commonly found in children and immunocompromised individuals (5,6); in children, cryptosporidiosis influences growth, physical activity, and cognitive function.…”
Section: Introductionmentioning
confidence: 99%